ANALISIS PAPARAN BENZENA PADA PETUGAS OPERTAOR SPBU DI WILAYAH KOTA MEDAN KECAMATAN MEDAN TIMUR - Susilawati Susilawati; Adelia Rahma (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
Heavy metal pollution including benzene is a serious problem in both developed and developing countries like Indonesia. Benzene pollution is closely related to mining processes, motor vehicle fumes and industries that use benzene raw materials such as fuel oil which contains toxic chemicals. Fuel oil can produce vapor or gas in the air which has a negative impact on human health. This study aims to determine the exposure of benzene to Pertamina gas station attendants in the East Medan District. This study used an analytic observational research design with a cross-sectional study approach. The sample in this study was taken using the total sampling method, namely 40 respondents. The results of this study were that there was a significant relationship between benzene exposure and the respondent's working hours with p=0.004, there was a significant relationship between benzene exposure and the respondent's working period with p=0.000, and a significant relationship between benzene exposure and smoking habits with a p=0.001. The conclusion of this study is that benzene can accumulate in the body for a long time. The accumulation of benzene in the body, especially for gas station workers, can be influenced by several factors, including long working hours, working hours that are more than normal working hours, and smoking habits. Apart from blood and urine specimens, benzene accumulation in a person's body can also be detected in other specimens such as hair because hair can store accumulated chemicals in the body for a long time.